Dual involvement of Caspase-4 in Inflammatory and ER Stress-induced Apoptotic Responses in Human Retinal Pigment Epithelial Cells - Bian, Zong-Mei (2009)
PURPOSE: To investigate the functional involvement of caspase-4 in human retinal pigment epithelial (hRPE) cells. METHODS: Expression and activation of caspase-4 in hRPE cells were measured after stimulation with pro-inflammatory agents IL-1β (2 ng/ml), TNF-α (20 ng/ml), lipopolysaccharide (1000 ng/ml), γ-interferon (500 U/ml), or monocyte co-culture in the absence or presence of immunomodulating agents cyclosporine (3 or 30ng/ml), dexamethasone (10 μM), or IL-10 (100 U/ml), as well as endoplasmic reticulum (ER) stress inducers thapsigargin (25 nM) or tunicamycin (3 or 10 μM). The onset of ER stress was determined by expression of GRP78. The Involvement of caspase-4 in inflammation and apoptosis was further examined by treating the cells with caspase-4 inhibitor ZLEVD-fmk, caspase-1 and -4 inhibitor Z-YVAD-fmk and pan-caspase inhibitor Z-VAD-fmk. RESULTS: Caspase-4 mRNA expression and protein activation were induced by all the pro-inflammatory agents and ER stress inducers tested in this study. Caspase-4 activation was blocked or reduced by dexamethasone, and IL-10. Elevated ER stress by pro-inflammatory agents and ER stress inducers was shown by increased expression of the ER stress marker GRP78. The induced caspase-4 and caspase-3 activities by tunicamycin, and the stimulated IL-8 protein expression by IL-1β were markedly reduced by caspase-4 inhibitor Z-LEVD-fmk. While caspase-4 inhibitor Z-LEVD-fmk and caspase-1 and -4 inhibitor Z-YVAD-fmk reduced tunicamycin-induced hRPE apoptotic cell death by 59 and 86%, respectively, pan-caspase inhibitor Z-VAD-fmk completely abolished the induced apoptosis. CONCLUSION: Caspase-4 is dually involved in hRPE pro-inflammatory and proapoptotic responses. Various pro-inflammatory stimuli and ER stress induce hRPE caspase-4 mRNA synthesis and protein activation. The ER stress-induced hRPE cell death is caspase- and, in part, caspase-4-dependent.